Análisis constitucional de la prohibición de auto incriminación y el procedimiento abreviado - Veintimilla Villavicencio, Juan Pablo (2023)
This article aims to conduct a constitutional analysis of the prohibition against self-incrimination and its application in the abbreviated procedure of the Ecuadorian criminal justice system. The principle of self-incrimination, recognized in Article 77 of the Constitution of Ecuador, implies that no one can be compelled to testify against themselves regarding facts that may imply their criminal liability. It is a fundamental guarantee that safeguards the right to defense and the presumption of innocence of citizens. However, the Comprehensive Organic Penal Code (COIP) establishes the abbreviated procedure as an alternative form of early termination of the criminal process, which requires the defendant to acknowledge their responsibility for the offense to access this benefit. This situation raises questions about the effective protection of the prohibition against self-incrimination. This article seeks to theoretically underpin the principle of self-incrimination, presenting a critical analysis of the essential elements of the expedited procedure and the accused's acknowledgment of responsibility, considering the recurrence of the offense. This issue is examined from a legal and constitutional perspective, to determine whether the expedited procedure in the Ecuadorian criminal justice system aligns with the fundamental principles of justice and respect for individual rights. The analysis draws on legislation, legal doctrine, relevant jurisprudence, and a documentary review of judgments. The research also relies on surveys conducted among lawyers, judges, and specialized educators from Loja. Among the surveyed individuals, 86.7 % are familiar with the prohibition of self-incrimination. Furthermore, 80 % believe that this principle supports the presumption of innocence, while 73.3 % do not perceive any infringement in the Ecuadorian criminal justice system. However, 46.7 % consider potential repercussions resulting from applying the expedited procedure. Opinions differ on adequate regulation and protection of the principle in Ecuador's criminal procedural law, with 60 % indicating that it is not sufficiently regulated. In conclusion, the research underscores concerns about the potential impact of the principle of self-incrimination on the expedited procedure, highlighting the importance of balancing procedural expediency and the safeguarding of fundamental rights within the Ecuadorian criminal justice system.